Students' experiences of cooperation with nurse teacher during their clinical placements: An empirical study in a Western European context - Saarikoski, Mikko; Kaila, Päivi; Lambrinou, Ekaterini; Pérez Cañaveras, Rosa María; Tichelaar, Erna; Tomietto, Marco; Warne, Tony (My University, 2013)
In many European countries during the last decade, the clinical role of the nurse teacher has changed from a clinical skilled practitioner to a liaison person working between educational and health care provider organisations.This study explored pre-registration nursing students' perceptions of cooperation with nurse teachers during their clinical placements in nine Western European countries. The study also assessed the type and range of e-communication between students and nurse teachers and whom the students' perceived as their most important professional role model.The study is a descriptive survey. Quantitative data were collected from 17 higher education institutes of nursing located in the northern, middle and southern parts of Europe. The purposive sample (N = 1903) comprised students who had participated in courses which included clinical placements. The data were analysed using descriptive statistics. Comparisons between the groups were made using cross-tabulation.The majority (57%) of students met their nurse teacher 1-3 times during their placement while 13% of the students did not meet their nurse teacher at all. Additionally, 66% of respondents used some form of e-communication (e-mail, mobile text messages etc.) to communicate with their nurse teacher.It is important to clarify the division of labour between nurse teachers and Mentors. There are both opportunities and challenges in how to utilise information technology to more effectively promote cooperation between students and nurse teachers.
Keywords: Clinical placements; Professional role modelling; E-communication; Nurse teacher; Nursing students